Hypomorphic NOTCH3 Alleles Do Not Cause CADASIL in Humans. Issue 11 (7th October 2013) - Rutten, Julie W.; Boon, Elles M.J.; Liem, Michael K.; Dauwerse, Johannes G.; Pont, Margot J.; Vollebregt, Ellen; Maat‐Kievit, Anneke J.; Ginjaar, Hendrika B.; Lakeman, Phillis; van, Sjoerd G.; Terwindt, Gisela M.; Lesnik Oberstein, Saskia A.J.
<x xml:space="preserve">Abstract</x> In this study, we address the previously unresolved issue of the role of hypomorphic NOTCH3 alleles in CADASIL. Based on extensive investigations of two families, we show that hypomorphic NOTCH3 alleles do not cause CADASIL. Furthermore, we describe the first patient who is compound heterozygous for a typical cysteine altering NOTCH3 missense mutation and a large intragenic NOTCH3 deletion who, interestingly, has a phenotype within the normal CADASIL spectrum. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>